John Eliot, John Veniaminov, and engagement with the indigenous peoples of North America: A comparative missiology, part I - Black, Joseph William (Missiology, 2020)
John Eliot was the 17th-century settler and Puritan clergyman who sought to engage with his Wampanoag neighbors with the Christian gospel, eventually learning their language, winning converts, establishing schools, translating the Bible and other Christian literature, even establishing villages of converted native Americans, before everything was wiped out in the violence of the King Philip War. John Eliot is all but forgotten outside the narrow debates of early American colonial history, though he was one of the first Protestants to attempt to engage his indigenous neighbors with the gospel. John Veniaminov was a Russian Orthodox priest from Siberia who felt called to bring Christianity to the indigenous Aleut and Tinglit peoples of island and mainland Alaska. He learned their languages, established schools, gathered worshiping communities, and translated the liturgies and Christian literature into their languages. Even in the face of later American persecution and marginalization, Orthodoxy in the indigenous communities of Alaska remains a vital and under-acknowledged Christian presence. Later made a bishop (Innocent) and then elected the Metropolitan of Moscow, Fr. John (now St. Innocent) is lionized in the Russian Church but almost unknown outside its scope, even in Orthodox circles. This 2-part article examines the ministries of these men, separated by time and traditions, and yet working in similar conditions among the indigenous peoples of North America, to learn something of both their missionary motivation and their methodology.